(untitled) (Bangladesh Journal of Agricultural Research, 2014)
The experiment was carried out with 32 genotypes of Brassica rapa including two commercially cultivated varieties as checks to study their mean, range, cv (%) correlation co-efficient, and path co-efficient considering 10 different morphological characters at the experimental farm of SAU, Dhaka during November 2009 to February 2010. Significant variation was observed among all the genotypes for all the characters studied except 1000-seed weight. In general, genotypic correlations were higher than the phenotypic correlations. It indicates that there was an inherent association among them which was adversely influenced by the environment. Days to flowering showed positive significant correlation with days to maturity. Plant height showed positive significant correlation with number of primary branches/plant. Number of primary branches/plant showed positive significant correlation with siliquae/plant. Length of siliquae showed positive significant correlation with seeds/siliquae. Number of secondary branches, number of siliquae/plant, days to maturity, seeds/siliquae, and 1000-seed weight showed positive significant association with yield/plant. Path analysis showed that number of primary branches/plant, number of siliquae/plant, number of secondary branches/plant, and number of seeds/siliquae had direct effect on seed yield/plant. Considering analytical findings of correlation co-efficient, path co-efficient analysis and field performance, the genotypes G-15, G-19, G-1, G-3, G-4, G-10, G-18 G-21, and G-24 would be suitable for future hybridization programme. DOI: http://dx.doi.org/10.3329/bjar.v38i4.18945 Bangladesh J. Agril. Res. 38(4): 599-612, December 2013